Effect of magnetic activity on the dynamics of equatorial F region irregularities - Bhattacharyya, A.; Basu, S.; Groves, K.M.; Valladares, C. E.; Sheehan, R. (My University, 2002)
[1] Two different aspects of the effect of magnetic activity on the dynamics of equatorial spread F (ESF) irregularities are studied here using spaced receiver scintillation observations. The first one deals with the question of how magnetic activity affects the generation of ESF irregularities. For this, a parameter designated the â€œrandom velocity,â€ which is a measure of random changes in the irregularity drift velocity, is evaluated from the data. In past studies, this parameter has been found to have large values in the early phase of evolution of ESF irregularities during the postsunset period, with a steep decline to a low value by 22 LT. This behavior is attributed to the decline in the height of the F region. Therefore, a sudden increase in the â€œrandom velocityâ€ in the postmidnight period is attributed to an increase in the height of the F region due to the ionospheric zonal electric field turning from westward to eastward due to the effect of magnetic activity, which may also generate fresh irregularities that produce the observed scintillations. This idea has been used to suggest that for two of the magnetically active days considered in the present study the irregularities may be freshly generated in the postmidnight period. The second aspect is the identification of geomagnetically disturbed plasma drifts, which is generally possible only after 22 LT, when the estimated irregularity drift velocities are close to that of the background plasma. The pattern of the estimated drift after 22 LT (3 UT) is found to be well defined for magnetically quiet days with scintillations during a period of a month. This allows the identification of a superimposed westward perturbation in the drift, produced by a disturbance dynamo due to magnetic activity, for all the three events studied here. On 19 February and 1 March 1999, the eastward drift velocities show an identical decrease of about 50 m/s from the undisturbed drift at 0440 UT. On 1 March, the decay phase of the storm sets in later, and the eastward velocity continues to decrease until 0530 UT, turning westward with a maximum decrease of about 80 m/s from the undisturbed drift. On 22 October 1999, which was more disturbed than these two days, the westward perturbation was larger, causing the drift velocity to turn westward around 5 UT and a decrease of nearly 150 m/s from the quiet time drift at 8 UT. The results are in broad agreement with some of the recent empirical models of the evolution, with storm time, of equatorial disturbance dynamo electric fields.
Keywords: Magnetic activity; Equatorial Spread F(ESF); ESF irregularities; Electric fields; Ionospheric dynamics; Ionospheric irregularities